Challenges to implementing greenhouse gas mitigation measures in livestock agriculture: A conceptual framework for policymakers. Issue 92 (February 2019) - Kipling, Richard P.; Taft, Helen E.; Chadwick, David R.; Styles, David; Moorby, Jon
Graphical abstract: Highlights: Challenges identified to implementing GHG mitigation measures in livestock systems. Practical, knowledge and cognitive limitations interact with interests. Cognitive limitations and critical perspectives of change highlighted. Conceptual model for policymakers links main types of challenge. Abstract: Livestock agriculture is a significant global emitter of greenhouse gases (GHG) and the sector is under pressure to reduce its environmental footprint. Dairy, sheep and beef production are major contributors to emissions. Here, a study of the barriers to implementing GHG mitigation measures on sheep, beef and dairy farms in Wales provides insights into challenges for these sectors globally. Data were gathered from 18 stakeholder organisations and farmers using semi-structured interviews and facilitated workshops. Participants were asked about the challenges to implementing measures associated with different parts of the farming system. Data were analysed using a grounded theory approach. Identified themes covered the range of challenges to the implementation of climate-friendly agricultural practice described in a global review. A conceptual model linking categories of challenge (Practical limitations, Knowledge limitations, Cognitive limitations and Interests) was developed from the data. Comparing the findings with existing work on behavioural change revealed two major differences: i) The concept of Cognitive limitations highlighted the importance of cognitive processes recognised in social psychology to the implementation of change in livestock agriculture. It differentiated specific cognitive biases incorporated in behavioural models from constraints affecting the thought processes in which these biases develop and which they affect, ii) Critical elements such as power relationships and conflicting stakeholder interests were highlighted as important factors outside the scope of behavioural change models. The conceptual model developed can support policymakers in understanding and tackling challenges to change in livestock agricultural systems.